The Impact of Organizational Culture on the Opportunities and Threats in Digital Transformation - Bálint Jakab; Nikoletta Kaszás; Ildikó Ernszt (International School for Social and Business Studies, 2023)
Purpose: The aim of the research is to show how the individual elements of the organizational culture - learning organization - affect the opportunities and threats related to the introduction of Industry 4.0. Study design/methodology/approach: A structured questionnaire was used to survey Hungarian companies. The online questionnaire with closed and measurable scale questions were created and distributed. Questions covered following: perceived and detected threats that may hinder organizations in the digital transition process, the benefits that businesses see as an opportunity in the digital transformation, by examining the most important variables of learning organizations and the opportunities and dangers of digital transformation. As a result, survey received a positive feedback with 639 fully completing the questionnaire. Measurement was performed using IBM SPSS Statistics (Version 22.) In the first stage of the research, an Opportunities and a Threats factor were created using principal component analysis. As a result, instead of seven and twelve variables, one can be used to examine additional relationships. In the next stage of the research, we examined how each element of the organizational culture (Organizational Culture - Learning Organization) affects the factors we created, what percentage they contribute to the formation of each factor. The measurement was performed by linear regression analysis. Findings: A comparison of two queries was performed, the results of which are summarized below. (A) How do certain elements of the organizational culture affect companies' the Industry 4.0 Opportunities? (B) How do certain elements of the organizational culture affect companies' Industry 4.0 Threats? In "A" case, the organizational culture factors explain 15.1% (R Square = .151) of the companies' Opportunity Factor. After the 5th modeling of the program, there are 5 Organizational Culture variables that significantly contribute to the Opportunities of companies. In "B" case, the Organizational Culture factors explain only 5.6% (R Square = .056) of the companies' Threats Factor. Following the 7th modeling of the program, there are 3 Organizational Culture variables that contribute significantly to the Threats of companies, Originality/value: The five Organizational Culture variables that significantly contribute to the Opportunities of companies are: The organization proactively anticipates change, The organization is looking for innovative, new solutions, not limited by the habit, The organization also focuses on long-term impacts when making decisions, In the operation and development of the organization, the effects of the changes on other organizational units are taken into account and, The aim is to jointly develop the learning and development skills of the members of the organization, group learning. The three Organizational Culture variables that contribute significantly to the Threats of companies are: The organization is open to environmental change, The aim is to jointly develop the learning and development skills of the members of the organization, Employees can act to achieve their personal vision, ie. free self-realization.